2002
DOI: 10.1007/bf03395425
|View full text |Cite
|
Sign up to set email alerts
|

Rats’ Response Rates for 1 % Sucrose When Food-Pellet Reinforcement is Upcoming: Effect Of Upcoming Reinforcement Contingency

Abstract: Previous research has demonstrated that rats' rates of lever pressing for 1 % liquid-sucrose reinforcers in the first half of a 50-min session increase when food-pellet, rather than the same sucrose, reinforcement will be delivered in the second half of the session. The present study investigated whether this increase (i.e., induction) would be influenced by alterations to the responsereinforcer relationship in the second half of the session. Experiment 1 manipulated this relationship by delaying reinforcers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(19 reference statements)
1
3
1
Order By: Relevance
“…On their face, the present results would seem inconsistent with those of Weatherly, Moulton, et al (2002), who found that the size of induction was reduced when the upcoming food pellets would be delivered independent of responding. Yet the results may not necessarily be at odds.…”
Section: Discussioncontrasting
confidence: 99%
“…On their face, the present results would seem inconsistent with those of Weatherly, Moulton, et al (2002), who found that the size of induction was reduced when the upcoming food pellets would be delivered independent of responding. Yet the results may not necessarily be at odds.…”
Section: Discussioncontrasting
confidence: 99%
“…For Group W-F, increasing the rate of foodpellet presentation in the second VI component produced a concomitant increase in lever pressing maintained by sucrose-water presentation, even though the rate of sucrose-water presentation was held constant in the first VI component. These data resembled those documented in several studies (e.g., Weatherly et al, 1999;Weatherly & Moulton, 2001;, and may qualify as induction because receiving food pellets in the second VI schedule, rather than sucrose water, might represent an improvement in the upcoming conditions of reinforcement (Weatherly et al, , 2002. Interestingly, however, we found the same result for Group F-W; lever pressing maintained by food pellets increased in the first VI component by increasing the rate of sucrose-water presentation in the second VI component.…”
Section: Determining the Relative Hedonic Value Of Food-pellet And Susupporting
confidence: 84%
“…In these studies of lever pressing maintained by 1 or 5 % of sucrose solution increased in the first VI if food-pellets, rather than the same sucrose solution, were delivered in the second VI. The interpretation of this result is that food-pellets delivered in the second half of the session represented an increase in the reinforcer value relative to either 1 or 5 % liquid-sucrose obtained in the first half of the session Stout, Davis & Melville, 2001;Weatherly, Stout, Rue & Melville, 2000, Weatherly, Moulton & Ritt, 2002Weatherly, Arthur & Tischar, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies Weatherly, Himle, et al, 2001;Weatherly et al, 2002;Weatherly, Stout, et al, 2000) have reported that response rates for sucrose increased when food pellet, rather than the same sucrose, reinforcement was available in the second half of the session. However, it is also possible that continued sucrose reinforcement actually decreases response rates.…”
mentioning
confidence: 93%
“…For example, subjects may increase their response rate for sucrose when food pellet reinforcement is upcoming, because they are readying themselves to respond at a high rate for the food pellets. However, Weatherly, Moulton, and Ritt (2002) found that upcoming food pellets increased operant response rates for 1% sucrose even when the pellets would be delivered independently of responding.…”
mentioning
confidence: 95%